PERANAN SOP PADA ORGANISASI PEMERINTAHAN KOTA SURABAYA DALAM PENINGKATAN KEPUASAN PELAYANAN KEPADA MASYARAKAT(Studi Di Bagian Umum dan Protokol Pemerintahan Kota Surabaya) - Junita, Tias Dwi (Universitas 17 Agustus 1945 Surabaya, 2017)
THE ROLE OF SOP IN ORGANIZATION OF SURABAYA CITY GOVERNMENT IN THE IMPROVEMENT OF SERVICE SATISFACTION TO COMMUNITY (Study In General Section and Surabaya City Government Protocol) This research titled SOP (Procedure Operational Standards) role in Surabaya Municipal Government Organization in Improving Service Satisfaction to the society (Study in General Division and Protocol of Surabaya Municipal Government).SOP role in the government institution service is essential. SOP as work guidance and Public service human resource performance measurement, with service comply with SOP also has effect on service satisfaction toward the society. The implementation of research object located in General Division and Protocol Office of Surabaya Municipal Government at Taman Surya 1 Surabaya. Method that used in this research by using qualitative descriptive method. Data analysis technique done, by using data presentation , data reduction, data display, and draw conclusion. Collection technique that used by the researcher are begin from interview of service staff/officers in General Division and Protocol Office of Surabaya Municipal Government , comprise of Division Head of General Division and Protocol Office, Secretary of Division Head of General Division and Protocol Office, and officers of General Division and Protocol Office , and several public people who using service in the General Division and Protocol Office. Field observation/research object , documentation and learning from existing yearly report in this office. The finding result taken by the research, show that what have done by researching SOP of General Division and Protocol Office of Surabaya Municipal Government, synchronizes at today service condition with exist SOP, then the result of the research can be explained that SOP role in improving service satisfaction to the society can not be successful yet because there are still to be improved again its service and human resource in order to make society satisfaction can be increased.Â Keywords : SOP, Service, Service satisfaction to the society